Delivering a quality-assured fracture liaison service in a UK teaching hospital—is it achievable?. Issue 10 (October 2016) - Shipman, K.; Stammers, J.; Doyle, A.; Gittoes, N.
Abstract Summary To determine whether new national guidance on the specifications of a fracture liaison service are realistically deliverable, 1 year of data on the performance of such a service were audited. Audit targets were mostly met. This audit demonstrates that these standards are deliverable in a real world setting. Introduction UK service specifications for a fracture liaison service (FLS) have been produced (National Osteoporosis Society, NOS) to promote effective commissioning and delivery of the highest quality care to patients with fragility fractures. How deliverable these standards are has not as yet been methodically reported. Our FLS was modelled on the ten NOS standards; performance was audited after 1 year to determine whether these standards could be delivered and to describe the lessons learnt. Methods Performance was audited against the NOS FLS Service Standards, with management based on the Fracture Risk Assessment Tool (FRAX®), the four-item Falls Risk Assessment Tool (FRAT), National Institute for Health and Care Excellence (NICE) and the National Osteoporosis Guideline Groups (NOGG) guidance. Data were recorded prospectively on a database. The FLS commenced in May 2014, was fully operational in August 2014 and data were captured from 1 September 2014 to 1 September 2015. Results The FLS detected 1773 patients and standards were largely achieved. Most, 94 %, patients were seen within 6 weeks, 533 DXA requests were generated, 804 outpatient FRAT assessments were recorded (134 required falls intervention) and 773 patients had bone treatments started. On follow-up at 3 months, between 78–79 % were still taking medication. Conclusions Preliminary evaluation of a FLS implemented according to UK NOS standards demonstrates that the model is practical to apply to a large teaching hospital population. Collection and review of outcome and cost effectiveness data is required to determine the performance of this model in comparison with existing models.